Preexisting Trichinella spiralis infection attenuates the severity of Pseudomonas aeruginosa-induced pneumonia. - Shao Rong Long; Wen Xuan Shang; Miao Jiang; Jing Fei Li; Ruo Dan Liu; Zhong Quan Wang; Hualei Sun; Jing Cui (PLoS Neglected Tropical Diseases, 2022)
Background A range of helminth species involve the migration of developing larvae through the lung and establish chronic infections in the host that include potent immune regulatory effects. Trichinella spiralis is one of the most successful parasitic symbiotes. After released by intestinal female adult worms, newborn larvae of T. spiralis travel through the circulatory system to the lung and finally reach skeletal muscle cells. As unique inflammation modulator of intracellular parasitism, T. spiralis shows improved responses to autoimmune disease and viral pulmonary inflammation by exerting immunomodulatory effects on innate and adaptive immune cells. Methodology/principal findings C57BL/6 mice were divided into four groups: uninfected; helminth- T. spiralis infected; P. aeruginosa infected; and co-infected. Mice infected with T. spiralis were incubated for 6 weeks, followed by P. aeruginosa intranasal inoculation. Bronchial alveolar lavage fluid, blood and lung samples were analyzed. We found that T. spiralis induced Th2 response in the mouse lung tissue, increased lung CD4+ T cells, GATA3, IL-4, IL-5 and IL-13 expression. Pre-existing T. spiralis infection decreased lung neutrophil recruitment, inflammatory mediator IL-1β and IL-6 expression and chemokine CXCL1 and CXCL2 release during P. aeruginosa- pneumonia. Furthermore, T. spiralis co-infected mice exhibited significantly more eosinophils at 6 hours following P. aeruginosa infection, ameliorated pulmonary inflammation and improved survival in P. aeruginosa pneumonia. Conclusions These findings indicate that a prior infection with T. spiralis ameliorates experimental pulmonary inflammation and improves survival in P. aeruginosa pneumonia through a Th2-type response with eosinophils.